Integrating government silos: Local emergency management and public health department collaboration for emergency planning and response - Fordham- Wolf, Susan (American Review of Public Administration)
The United States arguably faces the most serious disaster it has faced since World War II: the COVID-19 pandemic. The pandemic itself has created further cascading economic, financial, and social crises. To date, approximately 114,000 Americans have died and approximately 2,000,000 (as of this writing) have become infected. American emergency planning and response, including for pandemics, begins at the local (city, town, and county) level, close to the individuals and communities most impacted. During crises like COVID-19, natural and other disasters, best practices include (3z(Bwhole of government(3y (Band (3z(Bwhole community(3y (Bapproaches, involving all parts of the government, community organizations, institutions, and businesses, with representation from diverse individual community stakeholders. Local emergency management and public health agencies are at the heart of emergency planning and response and thus warrant further examination. While collaboration between the two is recognized as a best practice, in reality there appear to be silos and gaps. This Commentary describes the American emergency planning system and the roles of local emergency management and public health departments. Closer examination illuminates similarities and differences in practitioner demographics, professional competencies, organizational goals, and culture. The Commentary reviews the limited research and observations of collaboration efforts and suggests areas for integrating the two practice areas in future research, education, professional training, and practice. Breaking down the silos will strengthen local emergency and public health preparedness planning and response, ultimately leading to stronger community health, well-being, resilience, and more efficient local administration. - Reproduced s
Keywords: Public health preparedness, Emergency management, Emergencies, disasters, Pandemics, COVID-19, Coronavirus, local government collaboration